Pemanfaatan Limbah Jambu Mete sebagai Mordan dalam Proses Pencelupan - Muh Natsir; Hikmayani Hikmayani; Ahmad Zaeni (Universitas Negeri Makassar, 2020)
Abstract. Study concerning the utilisation of cashew apple (Anacardium occidentale L.) waste as mordant in dyeing process has been conducted. Cashew apple has a terrible astringent taste. The astringent comes from the composition of tannins of the fruit which is unliked by many people. In the other hand, tannin which is also caused a stain in cloth can use as natural mordant to bind dyes on fabric.Its tannin content makes cashew apple possible to be natural mordant. Mordant can be obtained through maceration using the solvent of ethanol which is acidified with HCl 1%. Effectivity test was performed by washing and absorbance measurement of 1'st and 2'nd of washing water by UV-Vis Spectrophotometer. The result showed that tannins of cashew apple could be used as mordant and the best results produced in mordanted fabric and fixed with fixator, ferrous sulphate.